2018
DOI: 10.1111/ajt.14690
|View full text |Cite
|
Sign up to set email alerts
|

A liver for a kidney: Ethics of trans-organ paired exchange

Abstract: Living donation provides important access to organ transplantation, which is the optimal therapy for patients with end-stage liver or kidney failure. Paired exchanges have facilitated thousands of kidney transplants and enable transplantation when the donor and recipient are incompatible. However, frequently willing and otherwise healthy donors have contraindications to the donation of the organ that their recipient needs. Trans-organ paired exchanges would enable a donor associated with a kidney recipient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…It would also be useful to increase the supply of deceased donors. Other avenues that might possibly increase the scope of exchange involve including other organs in exchanges (see Dickerson and Sandholm 2017;Sönmez and Ünver 2017;Samstein et al 2018).…”
mentioning
confidence: 99%
“…It would also be useful to increase the supply of deceased donors. Other avenues that might possibly increase the scope of exchange involve including other organs in exchanges (see Dickerson and Sandholm 2017;Sönmez and Ünver 2017;Samstein et al 2018).…”
mentioning
confidence: 99%
“…These include Hwang et al (2010) and Chan, Lo, Yong, Tsui, Ng, and Fan (2010), both of which demonstrated the proof of concept for liver exchange, and Mishra et al (2018), which advocated for organized liver exchange in the Unites States. Dickerson and Sandholm (2014) advocated for trans-organ exchange, where a donor associated with a kidney recipient donates a liver lobe and a donor associated with a liver recipient donates a kidney, whereas Samstein, de Melo-Martin, Kapur, Ratner, and Emond (2018) explored some of the ethical concerns this practice might encounter, including unbalanced donor risks. Ergin, Sönmez, and Ünver (2017) studied dual-donor organ exchange, where each patient receives organs from two living donors.…”
Section: Other Related Literaturementioning
confidence: 99%
“…mild reduction in glomerular filtration rate, a single kidney, a family history of kidney disease, complex anatomy, or history of kidney stones) but may still be an appropriate liver donor. This pair may match with another donor/recipient pair that needs a liver (Figure 2,(34))*. Liver donors with aberrant anatomy or insufficient hepatic mass may be appropriate kidney donors.…”
Section: Trans-organ Paired Exchangementioning
confidence: 99%